Systemic Administration of Tempol, a Superoxide Dismutase Mimetic, Augments Upper Airway Muscle Activity in Obese Zucker Rats - Baby, Santhosh M.; Tanner, Lisa H.; Discala, Joseph F.; Gruber, Ryan B.; Hsieh, Yee-Hsee; Lewis, Stephen J. (Frontiers in Pharmacology, 2022)
Obstructive sleep apnea (OSA) is characterized by repetitive partial/complete collapse of the pharynx during sleep, which results in apnea/hypopnea leading to arterial O2 desaturations and arousals. Repetitive apnea/hypopnea-arousal episodes cause hypoxia/reoxygenation cycles, which increase free radical generation and oxidative stress that cause motor/sensory nerve impairments and muscle damage. We hypothesize that antioxidants may protect from and/or reverse oxidative stress-induced damage in OSA patients. To understand the acute protective effects of antioxidants on respiratory muscles, we studied the systemic effects of a membrane permeable superoxide dismutase mimetic, Tempol, on genioglossus (EMGGG) and diaphragmatic (EMGDIA) electro-myographic muscle activities, hypoglossal motoneuron (HMN) output and cardiorespiratory parameters (mean arterial blood pressure, heart rate) in adult isoflurane-anesthetized obese Zucker rats (OZR) and age-matched lean Zucker rats (LZR). Tempol dose-dependently (1-100 mg/kg) increased EMGGG without changing EMGDIA in OZR and LZR. Tempol increased respiratory rate and tidal volume in OZR and LZR. Tempol (1-25 mg/kg) dose-dependently increased HMN output in healthy Sprague Dawley rats. Tempol (100 mg/kg) increased EMGGG output by 189% in OZR and 163% in LZR. With respect to mechanisms of effect, Tempol (100 mg/kg) did not augment EMGGG after bilateral HMN transection in Sprague Dawley rats. These data suggest that in addition to its known antioxidant and antihypertensive properties, Tempol can selectively augment EMGGG through modulating HMN activity and this effect may prevent collapsibility and/or improve stability of the upper airway pharyngeal dilator muscles during episodes of partial and/or complete collapse of the upper airway in OZR and perhaps in OSA human subjects.